2005
DOI: 10.1038/nature03702
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profiles classify human cancers

Abstract: Recent work has revealed the existence of a class of small non-coding RNA species, known as microRNAs (miRNAs), which have critical functions across various biological processes. Here we use a new, bead-based flow cytometric miRNA expression profiling method to present a systematic expression analysis of 217 mammalian miRNAs from 334 samples, including multiple human cancers. The miRNA profiles are surprisingly informative, reflecting the developmental lineage and differentiation state of the tumours. We obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

204
6,923
14
83

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 8,786 publications
(7,304 citation statements)
references
References 29 publications
204
6,923
14
83
Order By: Relevance
“…The function of miRNAs may be deregulated in cancer in several manners, including miRNA gene mutation, deletion or promoter hypermethylation, but also as a consequence of mutations in their target sequences (Esquela‐Kerscher and Slack, 2006; Nana‐Sinkam and Croce, 2011; Palmero et al., 2011). Although attenuated expression of the miRNA transcriptome is frequently observed (Kumar et al., 2007; Lu et al., 2005), various miRNAs are overexpressed in specific tumors compared to their healthy tissue of origin (Ma et al., 2010a,b; Volinia et al., 2006), and thus are termed “oncomiRs”. Furthermore, the predicted targets for several cancer‐associated miRNAs include protein‐coding tumor suppressors and oncogenes, supporting a role for miRNAs in cancer pathogenesis (Esquela‐Kerscher and Slack, 2006; Nana‐Sinkam and Croce, 2011; Palmero et al., 2011).…”
Section: Addressing Tumor Heterogeneity and Complexitymentioning
confidence: 99%
“…The function of miRNAs may be deregulated in cancer in several manners, including miRNA gene mutation, deletion or promoter hypermethylation, but also as a consequence of mutations in their target sequences (Esquela‐Kerscher and Slack, 2006; Nana‐Sinkam and Croce, 2011; Palmero et al., 2011). Although attenuated expression of the miRNA transcriptome is frequently observed (Kumar et al., 2007; Lu et al., 2005), various miRNAs are overexpressed in specific tumors compared to their healthy tissue of origin (Ma et al., 2010a,b; Volinia et al., 2006), and thus are termed “oncomiRs”. Furthermore, the predicted targets for several cancer‐associated miRNAs include protein‐coding tumor suppressors and oncogenes, supporting a role for miRNAs in cancer pathogenesis (Esquela‐Kerscher and Slack, 2006; Nana‐Sinkam and Croce, 2011; Palmero et al., 2011).…”
Section: Addressing Tumor Heterogeneity and Complexitymentioning
confidence: 99%
“…Research in a Caenorhabditis elegans model system revealed changes in miRNA expression in relation to lifespan and longevity (Boehm & Slack, 2005; Ibáñez‐Ventoso et al ., 2006; Pincus et al ., 2011). In humans, highly specific miRNA expression patterns are correlated with many age‐related diseases including cardiovascular disease (Small & Olson, 2011; Huan et al ., 2015c) and cancer (Lu et al ., 2005; Hayes et al ., 2014). Recent studies have examined differentially expressed miRNAs in relation to age in whole blood (ElSharawy et al ., 2012), peripheral blood mononuclear cells (PBMC) (Noren Hooten et al ., 2010), and serum (Noren Hooten et al ., 2013; Zhang et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible that upregulation of DICER1 may in part mediate metformin's antitumorigenic effects. In general with few exceptions, cancer cells have decreased global miRNA expression (Lu et al ., 2005; Kumar et al ., 2007), leading to the hypothesis that upregulation of DICER1 may lead to increased miRNA expression, which would then contribute to lowering tumorigenic activity. Consistent with this idea, DICER1 expression is decreased in several types of human cancers (Bahubeshi et al ., 2011; Foulkes et al ., 2014).…”
Section: Introductionmentioning
confidence: 99%